Analisis Pemberian Afiksasi Dan Kesalahan Ejaan Dalam Kutipan Pada Media Sosial Instagram - Yuli Siti Solihah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Writing a quote on social media is inseparable from the process of giving affixation and spelling errors, which can provide good examples or vice versa by showing inaccuracies in writing. Spelling mistakes in quotes on social media, one of which is instagram, can give bad habits in using correct Indonesian. The purpose of this research is to look for affixation and spelling errors found in quotes on instagram and correct them according to applicable rules. In this research using a descriptive method with a qualitative approach. Research data is in the form of words, phrase, clauses, and sentences contained in uploaded quotes on the accounts @note.batku, @fadelfikrif, and @kata_hati532. This research used data collection techniques, namely observation and documentation techniques. The result of the study found that there were (1) the process of giving affixation in the form of using prefixes, suffixes, and confixes; (2) spelling errors in the form of mistakes in writing words, word fragment, and capital letters. It is hoped that future researchers can choose deeper research thopics related to errors at the morphological level.